IMPLEMENTASI PENDIDIKAN MULTIKULTURAL MELALUI KEGIATAN FESTIVAL BUDAYA DI SANGGAR BIMBINGAN KAMUS GOMBAK UTARA - Fadhilah, Afiana; Hidayah, Alifah Nur; Hasanah, Asma Hidayatul; Fitriatun, Nofi; Rohayati, Sri; Hafni, Nurlaili Dina; Legowo, Yogi Ageng Sri (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2024)
Multicultural education is very necessary in dealing with conflicts in the era of the industrial revolution 4.0 which originate from ethnic, cultural, tribal and religious diversity. Multicultural education is very important especially for Indonesian children who were born and raised abroad. This study aims to strengthen multicultural education through cultural festival activities for students at the Kamus Guidance Center, North Gombak, Malaysia. This study uses a descriptive qualitative approach. The data collection techniques used were interviews, observation, and documentation. Observations were carried out on several aspects, including; (1) work plan observation, (2) observation of facilities and infrastructure; and (3) activity observation. Data analysis consisted of three stages, namely data reduction, data presentation, and drawing conclusions/verification. Multicultural education at SB Kamus North Gombak is very influential in creating good multiculturalism among students. Students become more tolerant of their friends who come from different religions, cultures and races. Students become more tolerant of their friends who come from different religions, cultures and races.